THE CRITICAL DISCOURSE ANALYSIS OF MISTRESS IN THE CASE OF LEGAL WIFE KILLED HER HUSBAND AFFAIRS NEWS - Sugianti Somba (Sekolah Tinggi Bahasa Asing LIA, 2022)
Abstract If there is a problem of infidelity, women are always admitted as inmates, and are stigmatized as other ideal women. When women, who get women become mistresses try to provide clarification on the accusations, this shows their resistance. This research has the title